1999
DOI: 10.1038/sj.bmt.1701921
|View full text |Cite
|
Sign up to set email alerts
|

Immunological reconstitution and correlation of circulating serum inflammatory mediators/cytokines with the incidence of acute graft-versus-host disease during the first 100 days following unrelated umbilical cord blood transplantation

Abstract: Summary:We investigated early immunological reconstitution and the production of circulating inflammatory mediators and their relationship to aGVHD in children during the first 100 days following unrelated UCBT. Nine patients had an underlying malignant disease (ALL, ANLL), and two, non-malignant diseases (SAA, ALD). The median age was 10 years (range: 1.25-21). Seven of 11 patients were alive by day 100, two died from regimen-related toxicity, and two died from severe aGVHD (grade уIII). Myeloid engraftment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
23
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 28 publications
7
23
1
1
Order By: Relevance
“…In contrast, we illustrated that myeloid engraftment in the NOD/SCID model in relation to the dose of CD34 + cells transplanted was comparable for UCB, BM and mPB. Our results may explain the clinical findings in UCB transplantation showing relatively high overall engraftment with high percentages and absolute numbers of B lymphocytes, [16][17][18] but delayed myeloid recovery caused by the relatively low numbers of CD34 + cells transplanted, 6,7 as compared to transplantation of bone marrow grafts. 19,20 …”
supporting
confidence: 70%
“…In contrast, we illustrated that myeloid engraftment in the NOD/SCID model in relation to the dose of CD34 + cells transplanted was comparable for UCB, BM and mPB. Our results may explain the clinical findings in UCB transplantation showing relatively high overall engraftment with high percentages and absolute numbers of B lymphocytes, [16][17][18] but delayed myeloid recovery caused by the relatively low numbers of CD34 + cells transplanted, 6,7 as compared to transplantation of bone marrow grafts. 19,20 …”
supporting
confidence: 70%
“…A related transplant, recipient's CMV sero-positive status and higher cell dose were associated with faster T-cell recovery, while this was delayed in the presence of acute GVHD. Other studies have reported similar results; 31,33,57 however, no correlation was found between NC dose and time to immune recovery 33 (Table 6). At 3 months after CBT immunoglobulin levels were normal, while numbers and function of T cells were significantly decreased, 56 in vitro responses to mitogen stimulation were detectable at 3 months after unrelated CBT and became normal at 6 months.…”
supporting
confidence: 72%
“…However, there are some reports of delayed immune recovery after CBT, in which transplant procedures involved ATG and mPSL for conditioning and GVHD prophylaxis. 21,22 In the present case, hematopoesis was supported by autologous hematopoietic recovery, and not comparable to previous studies that attained donor-derived complete chimerism. However, dysfunctional immunological reconstitution was observed soon after CBT, concurrently with irradiated autologous hematopoietic recovery.…”
Section: Total 20supporting
confidence: 60%
“…Although several studies have examined T cell recovery after CBT, 4,10,[20][21][22] little is known about immune reconstitution after myeloablative doses of irradiation. We documented the early immune reconstitution after a two loci HLA-mismatched CBT in an adult recipient compared to that seen with bone marrow, avoiding the use of ATG and mPSL in the conditioning and GVHD prophylaxis.…”
Section: Total 20mentioning
confidence: 99%